Estimation Analysis and Mapping the Need for ‘Agen Perisai’ in Expanding the Membership of BP Jamsostek (A Case Study of West Java Province, Indonesia) - Yulinda Nurul Aini (Journal of Indonesian Social Sciences and Humanities, 2020)
Social security is one indicator of human development efforts to achieve Indonesia's 2045 vision plan. One of the challenges in social security is the limited coverage and involvement of the population. In 2019, data of the BP Jamsostek West Java Province showed that the involvement of workers in the informal sector in social security was still low (around 3%). One of the efforts to increase the participation of informal workers is through Perisai agents. However, the number of active agents in West Java Province was still low and not comparable to the number of informal workers which reached 10 million people. Meanwhile in 2024, the government is targeting the participation of informal workers to be around 30% and universal coverage by 2029. For this reason, this article will form a scenario for estimating the need for Perisai agents to achieve universal coverage for informal worker participation. Based on the result, if the government want to achieve the target of 30% of informal workers' participation in 2024, the best scenario is to recruit 626 agents, while to achieve the universal coverage participation in 2029, the need for agents is 928 people. The highest agent needs are in the agriculture, wholesale trade, and accommodation sector. According to regency/city, the highest demand for agents is in the regencies of Bogor, Bandung, Garut, and Sukabumi. Furthermore, the mapping results by sector and regency/city can be used by relevant stakeholders to help formulate a Perisai agent recruitment policy to achieve universal coverage of BP Jamsostek membership in the coming year.